PENGARUH RASIO CAMEL, NPL, DAN PKMSA TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Indah Sugiarti, 09.05.52.0099; Badjuri, Achmad (Students Journal of Accounting and Banking, 2013)
The purpose of this research is to emperically study effect of Capital Adequacy Ratio (CAR), Produktive Asset Quality, Net Profit Margin (NPM), Operating Expenses and Operating Income , Loan to Deposite Ratio (LDR), non-performing loan (NPL) and Percent of Ownership Capital on stock price. This research is classified as causal research and replication of former researches. Population of this research are go public firms on Indonesia Stock Exchange (ISX) during the periode of 2008 to 2011. The samples are obtained by using purposive sampling method. As the result, from 31 go public firms, 21 are used as the samples of this study. The statistic method being used is multiple linear regression with the model being tested previously in classic assumptions. The result indicate that partially Capital Adequecy Ratio, Produktive Asset Quality, Net Profit Margin, Operating Expenses and Operating Income, Loan to Deposite Ratio (LDR), non-performing loan variable has significantly influenced the stock price, and partially Percent of Ownership Capital Stock Foreign has no significant influenced the stock price.Keywords: Capital Adequacy Ratio, Produktive Asset Quality , Net Profit Margin, Operating Expenses and Operating Income, Loan to Deposite Ratio, non-performing loan and Percent of Ownership Capital Stock Foreign, Stock Price